Paulo Freire : a critical encounter - McLaren, Peter, 1948-; Leonard, Peter, 1930- (Routledge, 1993)
Paulo Freire is regarded by many social critics as pe the twentieth century. This volume presents a pathfinding analysis by an international group of scholars.